The therapeutic role of oral tolerance in dextran sulfate sodium‐induced colitis via Th1–Th2 balance and γδ T cells. Issue 10 (2nd September 2013) - Yue, Min; Shen, Zhe; Yu, Chao Hui; Ye, Hua; Li, You Ming
Abstract : Objective: To evaluate the state of oral tolerance and its therapeutic role in mice with dextran sulfate sodium (DSS)‐induced colitis. Methods: Delayed‐type hypersensitivity (DTH) was determined 7 and 14 days after DSS‐induced colitis and control mice. Disease activity index (DAI) score and colonic histopathological score were measured 7 days after colonic extracted protein (CEP) or bovine serum albumin (BSA) (control) was administrated, with the evaluation of Th1–Th2 balance in the spleen, Peyer's patch and γδ T cells in intraepithelial lymphocytes and lamina proper lymphocytes in the intestine. Results: After fed with 250 μg ovalbumin oral tolerance was induced in 7 days in both DSS‐induced colitis and control mice, while oral tolerance persisted in the control mice but vanished in DSS‐induced colitis 14 days after ovalbumin challenge. DAI and colonic histopathological scores were decreased significantly after the ingestion of CEP (controlled by BSA) in DSS‐induced colitis with significant reduction of Th1 and the ratio of Th1 to Th2 in Peyer's patch as well as the γδ T cells in lamina proper lymphocytes in the intestine. No significant difference in Th1–Th2 balance in the spleen and γδ T cells in intraepithelial lymphocytes in the intestine were observed. Conclusions: There is a defect in oral tolerance at day 7 in DSS‐induced colitis. If taken orally, CEP may have a protective role in DSS‐induced colitis, which may be related to the deflection from Th1 to Th2 in Peyer's patch and the reduction of γδ T cells in lamina proper lymphocytes in the intestine.